Effect of Administration of Ramelteon, a Melatonin Receptor Agonist, on the Duration of Stay in the ICU: A Single-Center Randomized Placebo-Controlled Trial*. Issue 7 (July 2018) - Nishikimi, Mitsuaki; Numaguchi, Atsushi; Takahashi, Kunihiko; Miyagawa, Yasuhiro; Matsui, Kota; Higashi, Michiko; Makishi, Go; Matsui, Shigeyuki; Matsuda, Naoyuki
Abstract : Objectives: Occurrence of delirium in the ICU is associated with a longer stay in the ICU. To examine whether the use of ramelteon, a melatonin agonist, can prevent delirium and shorten the duration of ICU stay of critically ill patients. Design: A single-center, triple-blinded, randomized placebo-controlled trial. Setting: ICU of an academic hospital. Patients: Eligible patients were ICU patients who could take medicines orally or through a nasogastric tube during the first 48 hours of admission. Interventions: The intervention group received ramelteon (8 mg/d), and the control group received placebo (1 g/d of lactose powder) at 20:00 hours every day until discharge from the ICU. Measurements and Main Results: A total of 88 subjects were randomized to the ramelteon group (45 subjects) or the placebo group (43 subjects). As the primary endpoint, there was a trend toward decrease in the duration of ICU stay (4.56 d) in the ramelteon group compared with the placebo group (5.86 d) ( p = 0.082 and p = 0.028 before and after adjustments). As the secondary endpoints, statistically significant decreases in the occurrence rate (24.4% vs 46.5%; p = 0.044) and duration (0.78 vs 1.40 d; p = 0.048) of delirium were observed in the ramelteon group. The nonintubated patients of the ramelteon group showed statistically significantly fewer awakenings per night and a higher proportion of nights without awakenings. Conclusions: Ramelteon tended to decrease the duration of ICU stay as well as decreased the occurrence rate and duration of delirium statistically significantly. Abstract : Supplemental Digital Content is available in the text.